Segmental myoclonus as the presenting symptom of an acute disseminated encephalomyelitis: A case report - Kabakus, Nimet; Taskin, Erdal; Aydin, Mustafa (Elsevier Sci Ltd, 2006)
Segmental myoclonus is described as the involuntary contractions of contiguous muscles innerved by the brain stem or by spinal cord. The underlying causes of segmental myoclonus in children are demyelinating diseases and intrinsic tumors. Here, we report a case who was presented with segmental myoclonus on his left arm and later diagnosed as atypical monosymptomatic presentation of acute disseminated encephalomyelitis (ADEM). The case represents the first in the literature in which ADEM is considered as the possible cause of segmental myoclonus. Our findings demonstrate that: (i) in focal movement disorders such as segmental myoclonus, a careful neuroradiological examination of the neuroanatomical region for the possible presence of organic lesions might be rewarding, (ii) ADEM might be one of the potentially reversible causes of myoclonus. (c) 2006 European Journal of Paediatric Neurology. Published by Elsevier Ltd. All rights reserved.
Keywords: segmental myoclonus; acute disseminated encephalomyelitis (ADEM); children